The genus Syllis Savigny in Lamarck, 1818 (Annelida, Syllidae) from Australia. Molecular analysis and re-description of some poorly-known species - Álvarez-Campos, Patricia; Riesgo, Ana; Hutchings, Pat; Martín, Guillermo San (Zootaxa, 2015)
The taxonomy and phylogenetic relationships within Syllis Savigny in Lamarck, 1818, the type genus of the family Syllidae, are still a matter of debate because the group does not show clear synapomorphies and because of the lack of molecular data for many of the species. In order to help understand some of the phylogenetic relationships within the genus Syllis, we have performed a morphological revision of part of the material collected during decades by the Australian Museum staff, and provide molecular data for species not sequenced before. In particular, seven poorly known Australian species of the genus Syllis Savigny in Lamarck, 1818 have been re-described in detail and sequenced to analyze their phylogenetic position: Syllis broomensis n. comb., S. crassicirrata (Treadwell, 1925) n. comb., Syllis cruzi Núñez & San Martín, 1991, S. edensis (Hartmann-Schröder, 1989), Syllis gracilis Grube, 1840, Syllis picta (Kinberg, 1866) n. comb., and S. setoensis (Imajima, 1966). The results obtained indicate the paraphyly of Typosyllis and a possible new organization of Syllis, which contains at least four well-supported clades.